Comparison Study of Diaspot Rapid One Test and Advanced Quality Test in the Diagnosis of H. Pylori from Smokers - Fejer, Lamyaa Gh. (Universitas Muhammadiyah Sidoarjo, 2025)
Background :Helicobacter pylori is a microaerophilic, gram-negative bacterium that colonizes the human gastrointestinal tract and represents one of the most widespread bacterial infections globally. Several studies have shown a strong correlation between smoking and increased susceptibility to H. pylori infection, with smokers demonstrating a higher infection rate compared to non-smokers.Aims:This study aims to determine the most accurate and reliable diagnostic method for detecting H. pylori among smokers. Method:A comparative analysis was conducted between two rapid diagnostic tools: the Diaspot Rapid One Test and the Advanced Quality Rapid Anti-H. pylori Test. Both tests were applied to blood and stool samples collected from 100 male and female smokers at Al-Mustafa University College over a five-month period (September 2019–February 2020).Findings:Results revealed that 10% of the blood samples tested positive, whereas all stool samples returned negative results.Results:These findings suggest that stool testing may offer more accurate detection, as blood antibodies can persist even after the infection has resolved, potentially causing false positives. The study highlights the limitations of relying on a single diagnostic method, especially in smokers, and recommends the adoption of multimodal diagnostic approaches to enhance accuracy in high-risk populations. Highlights: Stool tests may be more accurate for current infections. Blood antibodies can cause false positives. Smokers are at higher risk for H. pylori infection. Keywords: Helicobacter Pylori, Smokers, Rapid Diagnostic Test, Stool Testing, Blood Antibody